Two-distance transitive normal Cayley graphs - Huang, Jun-Jie (Ars mathematica contemporanea, 2022)
In this paper, we construct an infinite family of normal Cayley graphs, which are 2-distance-transitive but neither distance-transitive nor 2-arc-transitive. This answers a question proposed by Chen, Jin and Li in 2019.
Keywords: 2-distance-transitive graph; 2-razdaljno tranzitiven graf; Cayley graph; Cayleyjev graf; enostavna grupa; simple group